2010
DOI: 10.1001/archsurg.2010.35
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Cholecystitis and a Complicated Clinical Course in Patients With Symptomatic Cholelithiasis

Abstract: For the patients with risk factors for AC, early cholecystectomy is recommended before the disease progresses to AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 28 publications
2
63
0
1
Order By: Relevance
“…Diabetics undergoing LC have a 2.5 times higher risk for CTO than nondiabetic patients (OR = 2.5; 95% CI: 1.3-4.4, P = 0.003) [43]. This might be because diabetic patients have a threefold greater risk for the development of AC than non-diabetics (OR 2.7; 95% CI: 1.8-4.2; P < 0.00005) [44]. Also, diabetics, especially if they are on insulin, have an 85% increased risk of preoperative GB perforation (adjusted OR = 1.85; 95% CI: 1.38-2.48; P < 0.001) [45].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 99%
“…Diabetics undergoing LC have a 2.5 times higher risk for CTO than nondiabetic patients (OR = 2.5; 95% CI: 1.3-4.4, P = 0.003) [43]. This might be because diabetic patients have a threefold greater risk for the development of AC than non-diabetics (OR 2.7; 95% CI: 1.8-4.2; P < 0.00005) [44]. Also, diabetics, especially if they are on insulin, have an 85% increased risk of preoperative GB perforation (adjusted OR = 1.85; 95% CI: 1.38-2.48; P < 0.001) [45].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 99%
“…1059 Patients who underwent laparoscopic cholecystectomy for symptomatic gallstones were taken in the period from 2004 to 2007 and found that the history of cerebrovascular accident (ischemic stroke or cerebral hemorrhage) was identified as an independent risk factor for acute cholecystitis. Approximately 85% of the patients who had a history of a cerebrovascular accident were presented with acute cholecystitis (7) . In the same context, the complication rate after the laparoscopic cholecystectomy for the patients with a history of CVA was also higher than for those patients without a history of CVA (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 85% of the patients who had a history of a cerebrovascular accident were presented with acute cholecystitis (7) . In the same context, the complication rate after the laparoscopic cholecystectomy for the patients with a history of CVA was also higher than for those patients without a history of CVA (7) . On the other side, a study was conducted on a convenience sample of 24 patients with an acute cholecystitis after an acute cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study found an increased risk of biliary diseases in patients with type 2 diabetes [5]. Furthermore, diabetes has been reported to be one of risk factors for acute cholecystitis and a complicated clinical course in patients with symptomatic cholelithiasis [1]. Therefore, we are apt to diagnose diabetic patients manifesting symptoms of cholecystitis as having cholecystitis due to bacterial infection and cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has been reported to be one of risk factors for acute cholecystitis and complicated clinical course in patients with symptomatic cholelithiasis [1]. Gallbladder motility is significantly impaired in diabetic patients due to autonomic neuropathy as compared with healthy subjects [2-4].…”
Section: Introductionmentioning
confidence: 99%